Long-term survivorship in multiple endocrine neoplasia type 2B diagnosed before and in the new millennium - Raue, Friedhelm; Dralle, Henning; Machens, Andreas; Bruckner, Thomas; Frank-Raue, Karin (The journal of clinical endocrinology & metabolism, 2018)
The present study of 75 patients with multiple endocrine neoplasia type 2B demonstrates long-term survival and improved outcomes in the new millennium.
First published online: 25 October 2017
Gesehen am 08.05.2019